Inoculation of apple plantlets with Rhodococcus pseudokoreensis R79T enhances diversity and modulates the structure of bacterial rhizosphere communities in soil affected by apple replant disease - Sarah Benning; Fatma M. Mahmoud; Pamela Espindola-Hernandez; Benye Liu; Karin Pritsch; Viviane Radl; Jana Barbro Winkler; Traud Winkelmann; Ludger Beerhues; Michael Schloter (BMC Plant Biology)
Abstract Background Apple replant disease (ARD) represents a dysbiotic rhizosphere condition potentially driven by root exudates including phytoalexins at the root–soil interface. A promising mitigation strategy could be the application of bioinoculants that reduce these compounds and foster a diverse microbiome. This study investigated the effects of Rhodococcus pseudokoreensis R79T, a strain with benzoate-degrading capabilities and genetic potential to degrade biphenyls, on the rhizosphere microbiome of apple plantlets grown in ARD-affected soil in a greenhouse experiment. Results We applied R79T at 10⁶ to 10⁹ CFU/ml, assessing its impact on bacterial 16S rRNA diversity and abundance, as well as the abundance of biphenyl dioxygenase (bphd) genes. Eight weeks post-inoculation reads of strain R79T persisted in the rhizosphere, particularly at higher inoculation levels. Inoculation enhanced bacterial diversity and bphd gene abundance, with significant shifts in community composition. Key responders included members of Gaiellales, which increased, and Streptomyces, which decreased. Co-occurrence network analysis revealed that inoculation promoted positive interactions, more homogeneous connectivity, and a higher degree of connections. Effects on bacterial community structure varied significantly with inoculation concentration. Conclusions The fact that R79T enhanced rhizosphere bacterial diversity and modulated community composition in ARD-affected soil highlights the potential of R79T to reshape microbial interactions. Further research is needed to elucidate the mechanisms underlying these effects, including studies on in situ degradation of phytoalexins and inoculation of R79T alongside bacteria for plant growth promotion (PGP) in synthetic communities for elevated efficiency against ARD.